KEKALAHAN INCUMBENT DALAM PEMILIHAN PENGHULU DI KEPENGHULUAN SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Muhammad Abdul Hadi; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Selection of Penghulu carried out simultaneously and surging throughout kepenghuluan in the region Rokan Hilir district. pemerilan pemulu here means the election of the village head where the village rokan hilir called the village with kepenghuluan and village chief called penghulu this is based on the efforts of the district government in order not to loss of unidirectional value for the society rokan downstream.The author conducted a research background on the election conducted in kepenghuluan sekeladi where in followed by five candidates, where each candidate to get a sound that is almost balanced there is only one candidate who get very low when compared with other candidates. Candidates who get a very low vote earning here is an incumbent candidate. This is what makes us as the authors want to conduct research to cause low incumbent candidate votes in the selection of penghulu.This study we as the authors review with two indicators of voter behavior and political marketing (strategy kompanye). Choosing Behavior Simply defined as the decision of a voter to vote for a candidate or a particular in the election. While Political Marketing is a political campaign strategy to form a certain set of political meanings in the minds of the voters.This research uses "multiple method" that is merging between quantitative and qualitative methods, in this case is the spread of questionnaires and interviews. Types of research data are primary data and secondary data, Data collection techniques used are questionnaires and interviews, Data analysis techniques used in this study using quantitative descriptive methods Data analysis techniques in this study is also reinforced by qualitative data.The results show that incumbent candidate is seen from the aspect of voter behavior and kompaye strategy has not been able to influence society to choose it. This is seen from the variable and indicator that the author set when doing research dikepenghuluan sekeladi.Keywords: Selection of Penghulu, Voter Behavior, Political Marketing (Strategy Kompanye)